Reliability and validity of 30-15 intermittent fitness test for cardiorespiratory fitness assessment among infantry members of Slovenian armed forces: A study protocol - Paravlic, Armin H.; Simunic, Bostjan; Pisot, Rado; Rauter, Samo; Vodicar, Janez (Frontiers in Psychology, 2022)
Introduction Cardiorespiratory fitness (CRF) testing is routinely performed by most armed and tactical forces around the world as part of their recruitment process for new members or simply as an annual examination of their personnel. A 2-mile run (2MR) test is among the most commonly used. However, as it is performed outdoors, weather, climate, and terrain can influence the results and often limit the maximum performance. Also, this test has been shown to be difficult for individuals because the pacing strategy is self-paced. As such, it does not reflect the real situation on the battlefield, where most activities are externally driven by the environment and the enemy. Therefore, we believe that the 30-15 Intermittent Fitness Test (30-15IFT) may be a suitable tool for measuring CRF and battle readiness of military personnel. Moreover, given the importance of visual attention to military personnel we aim to investigate the differences in visual attention between better and less physically prepared infantry members and its corresponding response to maximal endurance running test. Methods and analysis This randomized cross-over study using a within-subjects test-retest design will enroll 32 male infantry members of the Slovenian Armed Forces. To investigate the reliability and validity of the 30-15IFT test an incremental treadmill test (TR), a 2MR test, and two identical 30-15IFT will be performed in randomized order. Additionally, participants will be subsequently divided into two groups based on their score on the Army Physical Fitness Test (APFT), whereas differences in visual attention will be assessed by using the d2 test. The primary analysis will assess differences in key physiological outcomes between the different CRF tests (TR vs. 2MR vs. 30-15IFT). In addition, the relative reliability of all dependent variables between two 30-15IFT trials will be estimated by interclass correlation coefficient (ICC), while the relationship between maximal oxygen uptake, heart rate and maximal running speed of 30-15IFT, TR and 2MR will be assessed using Pearson’s correlation. Ethics and dissemination Ethical approval was obtained from the National Medical Ethics Committee (reference number: 0120-495/2021/6). The results of the proposed study will be disseminated through publication in peer-reviewed journals. Trial registration number: NCT05218798